Suppression Method for Smeared Spectrum Jamming Based on Lv’s Distribution Combined with Biorthogonal Fourier Transform - Zhenming Wen; Guohong Wang; Hongbo Yu (Journal of Electrical and Computer Engineering)
Smeared spectrum (SMSP) jamming is a deceptive jamming technique commonly used against linear frequency modulation (LFM) radar. This technique produces high-density false targets that resemble a comb shape after pulse compression processing, resulting in both deceiving and suppressing effects. In order to suppress jamming effectively, a new antijamming technique has been proposed that combines Lv’s distribution (LVD) with biorthogonal Fourier transform (BFT). The main idea of this antijamming method is based on a three-step process: “parameter estimation—echo modulation—identification and suppression.” The first step involves obtaining the delay and chirp rate of the jamming from the LVD matrix of the radar echo. Based on the estimated parameter information, a reference signal is designed to modulate the jamming into a complete chirp signal. In the second step, biorthogonal Fourier transform is used to distinguish between the target’s echo and jamming based on the difference in the chirp rate. Finally, jamming is filtered using narrow-band filtering in the chirp rate domain, and the original echo is recovered by using biorthogonal inverse Fourier transform (IBFT). Simulation results demonstrate that the proposed method achieves high accuracy in estimating jamming parameters and is capable of suppressing false targets under high jamming-to-signal ratio (JSR) conditions.